2010
DOI: 10.1016/j.schres.2009.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing subjective quality of life in patients with schizophrenia and other mental disorders: A pooled analysis

Abstract: Subjective quality of life (SQOL) is an important outcome in the treatment of patients with schizophrenia. However, there is only limited evidence on factors influencing SQOL, and little is known about whether the same factors influence SQOL in patients with schizophrenia and other mental disorders. This study aimed to identify the factors associated with SQOL and test whether these factors are equally important in schizophrenia and other disorders. For this we used a pooled data set obtained from 16 studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
66
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 48 publications
15
66
2
5
Order By: Relevance
“…Similarly, the previously mentioned Nysam study found no significant difference in this regard [53]. This finding is in line with, for instance, a pooled analysis of 16 studies (using MANSA or LQOLP) to study factors influencing subjective quality of life in patients with schizophrenia and other mental disorders, where it was found that gender did not have an effect [55]. Likewise, using the LQOLP instrument, it was found in a study with schizophrenia patients in the Netherlands that gender was not related to general quality of life [56].…”
Section: Differences In Subjective Dimensionssupporting
confidence: 85%
“…Similarly, the previously mentioned Nysam study found no significant difference in this regard [53]. This finding is in line with, for instance, a pooled analysis of 16 studies (using MANSA or LQOLP) to study factors influencing subjective quality of life in patients with schizophrenia and other mental disorders, where it was found that gender did not have an effect [55]. Likewise, using the LQOLP instrument, it was found in a study with schizophrenia patients in the Netherlands that gender was not related to general quality of life [56].…”
Section: Differences In Subjective Dimensionssupporting
confidence: 85%
“…The limited agreement between consumers and providers perspectives on consumers' QoL is important due to its putative relevance for the quality of the therapeutic relationship which is an important component of effective mental health care (Priebe et al 2005(Priebe et al , 2010Couture et al 2006;Lasalvia and Ruggeri 2007). A widely accepted definition of the therapeutic alliance characterizes it in terms of three core dimensions: a positive emotional relationship, agreement with regard to tasks, and consensus with regard to the goals of therapy (Bordin 1979;Horvath and Bedi 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As well as the 5 symptom sub-scales, age and gender were included in the analysis as research has shown that age tends to be positively related to global life satisfaction [4] and gender may also play a role [5, 6]. …”
Section: Methodsmentioning
confidence: 99%
“…We conducted an individual patient data meta-analysis to identify which psychopathological symptoms are associated with satisfaction with mental health. We also explored the influence of age and gender because previous research has suggested that age may be positively linked to life satisfaction [4], whilst findings concerning gender have been mixed, with studies coming to opposing conclusions regarding which gender tends to be associated with a higher life satisfaction [5, 6]. …”
Section: Introductionmentioning
confidence: 99%